Evaluating value requirement for Industrial Product-Service System in circular economy for wind power-based renewable energy firms. (15th March 2022) - Nag, Ujjwal; Sharma, Satyendra Kumar; Padhi, Sidhartha S.
Abstract: In India, Wind farms have been operating with obsolete wind energy generator and are facing troubles due to the end-of-service life of the wind turbines and other components. Only two options are available to the wind farms under such a scenario-repowering or life extension. At present, life extension is the only plausible solution to aging wind turbine as repowering initiative has been very slow due to many reasons. Life extension of wind turbine generates circular value and includes reconditioning of parts, reuse of few components, and finally remanufacturing. To achieve circular value, wind turbine original equipment manufacturers (WT OEMs) need to redesign their products and services to meet customer expectations. Literature hasn't discussed value requirements in the design and development of the Industrial Product-Service System (IPS 2 ) for the life cycle extension of product such as wind turbines. To address this gap, we proposed a research framework, which is composed of two stages – first deals with the elicitation of value requirement, and second describes the evaluation methodology to prioritize and rank the value requirement with Fuzzy AHP. Stage-I reveals that there are five customer value elements (Pre-sales Services, Product Reverse Flow, Refurbished Product Services, Installation and Site Services, Repair, Upgrade, and Debugging Services) catering to the circular services and two elements (Product differentiation and Benchmarking, Optimized Performance) catering to circular product. The analysis step in stage-II reveals that Repair, Upgrade, and Debugging (RUD) has got the highest priority and value requirement named as "Improved perceived performance" and "Smart monitoring" has got the highest weight under this category. This study contributes to the literature on product-service system, circular economy, and requirement engineering and puts forward theoretical and practical implications in the above area.